Sensorimotor training during expression of the leg extension response (LER) in 1‐day‐old rats. Issue 7 (29th August 2014) - Belnap, Starlie C.; Allmond, Jacob T.; Boomhower, Steven R.; Roberto, Megan E.; Brumley, Michele R.
ABSTRACT In newborn rats, the leg extension response (LER) is a coordinated hyperextension of the hindlimbs that is shown in response to anogenital stimulation. Here we examined the influence of sensorimotor training on LER expression in postnatal day 1 rats. In Experiment 1, we examined if proprioceptive feedback facilitates LER expression. We did this by repeatedly stimulating the pup's anogenital region with a vibrotactile device, to experimentally evoke the LER, thus increasing LER‐relevant hindlimb proprioceptive feedback during training. In trained subjects, the LER was evoked every 4 min for 15 trials, followed by a final LER test. Results indicated that proprioceptive feedback on its own did not alter later expression of the LER. In Experiment 2, we examined the effect of both proprioceptive and cutaneous feedback on LER expression, through the use of a range of motion (ROM) restriction during training. During ROM restriction, a Plexiglas plate was placed beneath the pup at 50% of limb length. After the 15th training trial, a final LER test occurred with no ROM restriction in place. Compared to controls, pups that experienced ROM restriction exhibited a significantly shorter LER duration, and smaller hip and ankle angles during the LER test (indicating greater limb flexion). Together these findings show that concurrent proprioceptive and cutaneous feedback, but not proprioceptive feedback alone, has persistent effects on expression of this newborn action pattern. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1553–1563, 2014.